Bacterial oncogenesis in the colon. (April 2013) - Dejea, Christine; Wick, Elizabeth; Sears, Cynthia L
The human colon plays host to a diverse and metabolically complex community of microorganisms. While the colonic microbiome has been suggested to contribute to the development of colorectal cancer (CRC), a definitive link has not been made. The role in which the colon microflora could contribute to the initiation and/or progression of CRC is explored in this review. Potential mechanisms of bacterial oncogenesis are presented, along with lines of evidence derived from animal models of microbially induced CRC. Particular focus is given to the oncogenic capabilities of enterotoxigenic Bacteroides fragilis . Recent progress in defining the microbiome of CRC in the human population is evaluated, and the future challenges of linking specific etiologic agents to CRC are emphasized.